Did Music Cause the End of the World? - J. Martin Daughtry (Transposition)
This essay seeks to clarify the relationship between music and environmental violence. After a reflection on the distortions and insights that different frames of reference produce, it places music within an expansive environmental register that encompasses the entirety of human history, up to and including our current era of “slow violence,” industrial pollution, mass extinction, and global warming. Throughout, human musicking is presented as always-already entangled with nonhuman entities and processes. The essay focuses on four of music’s potentialities—its exclusivity, centripetality, instrumentality, and reductivity—and argues that the cumulative effect of musicking has been to help perpetuate a type of anthropocentrism that made industrial-scale environmental violence possible. It concludes by suggesting a number of small tactics for musical thriving in an age when, in Timothy Morton’s words, “the concept of world is no longer operational”.